Neuroendocrine regulation of appetitive ingestive behavior - Keen-Rhinehart, Erin; Ondek, Katelynn; Schneider, Jill (Frontiers in Neuroscience, 2013)
Food availability in nature is often irregular, and famine is commonplace. Increased motivation to engage in ingestive behaviors increases the chance of survival, providing additional potential opportunities for reproduction. Because of the advantages conferred by entraining ingestive behavior to environmental conditions, neuroendocrine mechanisms regulating the motivation to acquire and ingest food have evolved to be responsive to exogenous (i.e. food stored for future consumption) and endogenous (i.e. body fat stores) fuel availability. Motivated behaviors like eating occur in two phases. The appetitive phase brings animals into contact with food (e.g. foraging, food hoarding), and the more reflexive consummatory phase results in ingestion (e.g., chewing, swallowing). Quantifiable appetitive behaviors are part of many the natural ingestive behavioral repertoire of species such as hamsters and humans. This review summarizes current knowledge about neuroendocrine regulators of ingestive behavior, with an emphasis appetitive behavior. We will discuss hormonal regulators of appetitive ingestive behaviors, including the orexigenic hormone ghrelin, which potently stimulates foraging and food hoarding in Siberian hamsters. This section includes a discussion of the hormone leptin, its relation to endogenous fat stores, and its role in food deprivation-induced increases in appetitive ingestive behaviors. Next, we discuss how hormonal regulators interact with neurotransmitters involved in the regulation of ingestive behaviors, such as NPY, AgRP and alpha-MSH, to regulate ingestive behavior. Finally, we discuss the potential impact that perinatal nutrient availability can have on the neuroendocrine regulation of ingestive behavior. Understanding the hormonal mechanisms that connect metabolic fuel availability to central appetite regulatory circuits should provide a better understanding of the neuroendocrine regulation of the motivation to engage in ingestive behavior.